GTSE1 promotes cell migration and invasion by regulating EMT in hepatocellular carcinoma and is associated with poor prognosis - Wu, Xiaojuan (Sci Rep, 2017)
G2 and S phase-expressed-1 (GTSE1) regulates G1/S cell cycle transition. It was recently reported to be overexpressed in certain human cancers, but its significance and mechanism(s) in hepatocellular carcinoma (HCC) remain unknown. Here, we showed preferential GTSE1 upregulation in human HCC tissues and cell lines that positively correlated with Ki67. GTSE1 knockdown by short hairpin RNA resulted in deficient colony-forming ability and depleted capabilities of HCC cells to migrate and invade. Conversely, exogenous GTSE1 overexpression enhanced colony formation and stimulated HCC cell migration and invasion. Furthermore, GTSE1 silencing was associated with the downregulation of N-cadherin, β-catenin, and Snail, whereas GTSE1 overexpression caused the opposite effects. GTSE1 upregulated Snail via both transcription and protein degradation pathways. Additionally, GTSE1 modulated the sensitivity of HCC to 5-fluorouracil therapy. High GTSE1 correlates with chemo-resistance, while low GTSE1 increases drug sensitivity. Kaplan-Meier survival analysis indicated that high GTSE1 levels were significantly associated with poor overall survival. In conclusion, high expression of GTSE1 is commonly noted in HCC and is closely correlated with migration and invasion by epithelial-to-mesenchymal transition (EMT) modulation. Activated GTSE1 significantly interferes with chemotherapy efficacy and influences the probability of survival of patients with HCC. GTSE1 may thus represent a promising molecular target.